Proceeding for Recent Trends in Biomedical Sciences-2018 (RTBS-2018) - Medical Labor, Organised By Department Of (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Organised by Department of Medical Laboratory Sciences, Lovely Professional University Punjab Smt. Shanti Devi Mittal Auditorium, Lovely Professional University Punjab on 16th March 2018 (Friday)